Corruption, Public Investment, and Growth - Tanzi, Vito.; Davoodi, Hamid (Washington, D.C. : International Monetary Fund, 1997)
Corruption, particularly political or 'grand' corruption, distorts the entire decision-making process connected with public investment projects. The degree of distortions is higher with weaker auditing institutions. The evidence presented shows that higher corruption is associated with (i) higher public investment; (ii) lower government revenues; (iii) lower expenditures on operations and maintenance; and (iv) lower quality of public infrastructure. The evidence also shows that corruption increases public investment while reducing its productivity. These are five channels through which corruption lowers growth. An implication is that economists should be more restrained in their praise of high public sector investment, especially in countries with high corruption.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet